The Relationship between Verbal Bullying and Students' Learning Motivation at SMP Negeri 1 Pakis - Ambawani, Adjie Satrio; Rosyidah, Arini Hanna; Khasana, Luthfi Nur; Prihatiningsih, Riskiyana (Proceedings Series of Educational Studies, 2024)
Verbal bullying is an openly degrading act in the form of unkind calls, taunts and words of a sexual nature that occurs to both boys and girls which is often not realized and occurs because there is no adult supervision. The aim of this research is to find out whether verbal bullying behavior has a relationship with students' learning motivation at SMPN 1 Pakis or not. The method used is a quantitative research design with correlational analytics using Pearson Correlation with random sampling techniques. Based on the results of the Pearson Correlation test between the variables verbal bullying and learning motivation, a significance value (p) = 0.477 (p>0.05) was obtained, which means the hypothesis is not accepted. The correlation coefficient value is 0.076, which means there is no relationship between the verbal bullying variable and learning motivation, which means the hypothesis is not accepted.